Analysis of Slang Language Used by Malaysian K-Pop Fans on Twitter - Siti Marina, Kamil; Mun, Poh Yan (2022)
In this era of digital technology, one of the most extensively used internet slang is the K-Pop slang. The slang is used by K-Pop fans to interact on social media platforms including Twitter. In Malaysia, KPop fans refer to those who love Korean music and drama including Korean movies. Cho (2010) stated that the Korean entertainment industry has created a very positive perception of Korea and its people among Malaysians, resulting in the growing number of those who idolised the Korean entertainment industry. MediaBUZZ (2019) reported that Malaysia is among the top 20 countries where users tweeted about K-Pop the most. The omnipresence of K-Pop content in various platforms of Malaysian media has enabled the Malaysian K-Pop fans to further indulge in the culture of their idols, especially their language use. They imitate their language to express their love and thoughts through fandom accounts. Gan (2019) reported that Malaysians are willing to learn the Korean language under the influence of KPop because of the overwhelming influence of the modern popular culture in Malaysia. Previous studies on the influence of K-Pop on Malaysian youth has been carried out extensively by Nor Hashimah & Zahrani (2011), Ariffin, Othman & Abdullah (2013), Zailin Zainal Ariffin et. al (2016), Mazdan & Lau, M.W (2018), and Nor Khairin (2020) among others. The aspects focused on were more on the sociocultural dimensions as well as the consumerism of K-Pop brands. This paper aims to examine the slang language used by Malaysian K-Pop fans on Twitter, specifically on the types and functions of the slang language.